2007
DOI: 10.1055/s-2006-958469
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Decidualization in Regulating Endometrial Hemostasis during the Menstrual Cycle, Gestation, and in Pathological States

Abstract: Progesterone-induced decidualized human endometrial stromal cells form a hemostatic envelope that protects against hemorrhage during invasion of endometrial capillaries by implanting blastocyst-derived cytotrophoblasts (CTs). This hemostatic milieu reflects co-upregulated expression of tissue factor (TF), the primary initiator of hemostasis via thrombin generation and plasminogen activator inhibitor type 1, which inactivates tissue-type plasminogen activator, the primary fibrinolytic agent. During deep invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 32 publications
(48 reference statements)
0
50
0
2
Order By: Relevance
“…Metformin also has beneficial effects on endometrial abnormalities, such as hyperplasia and cancerous lesions (Palomba et al 2009). Expression of the insulin receptor gene is regulated during the menstrual cycle, enabling insulin to inhibit stromal cell decidualization (Lockwood et al 2007). Recent evidence suggested that metformin inhibits hepatic gluconeogenesis by inhibiting mitochondria complex I activity (Owen et al 2000) and activating its downstream target, AMPK, which can regulate multiple signaling pathways controlling cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin also has beneficial effects on endometrial abnormalities, such as hyperplasia and cancerous lesions (Palomba et al 2009). Expression of the insulin receptor gene is regulated during the menstrual cycle, enabling insulin to inhibit stromal cell decidualization (Lockwood et al 2007). Recent evidence suggested that metformin inhibits hepatic gluconeogenesis by inhibiting mitochondria complex I activity (Owen et al 2000) and activating its downstream target, AMPK, which can regulate multiple signaling pathways controlling cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…While preterm PROM is associated with the activation of the decidua and the membranes, myometrial activation is the major component of preterm labor with intact membranes 58 . This is relevant because the decidua and the membranes have a high TF concentration 17,18,59 . In summary, the evidence brought herein suggests that increased thrombin generation in patients with the great obstetrical syndromes may reflect the activation of the coagulation cascade mainly through the extrinsic arm.…”
Section: Changes In the Hemostatic System Of Women With Obstetrical Smentioning
confidence: 99%
“…During this deep invasion step, EVT opened and remodelled spiral arteries and arterioles to produce high-conductance vessels, necessary for the further developing fetus. The haemostasis into decidua during vessel invasion was ensured by up-regulation of tissue factor (TF) and activation of extrinsic coagulation cascade, and simultaneously increased PAI-1 activity [41]. The result of increased TF activity is generation of thrombin.…”
Section: Overview Of Human Embryo Implantation Stages Adhesion Glycomentioning
confidence: 99%
“…The result of increased TF activity is generation of thrombin. In cases of increased thrombin production, such as in inherited thrombophilias conditions, the decidual cells produced anti-angiogenic soluble fmslike tyrosine kinase-1 factor (sFlt-1), which inhibits enzymes related with EVT invasion [41]. Insufficient shallow invasion of ECT into decidua results in incomplete vascular transformation and underperfused embryonic cells, which could lead to early pregnancy loss.…”
Section: Overview Of Human Embryo Implantation Stages Adhesion Glycomentioning
confidence: 99%
See 1 more Smart Citation